gRNA Sequence Heterology Tolerance Catalyzed by CRISPR/Cas in an In Vitro Homology-Directed Repair Reaction - Amanda M. Hewes; Brett M. Sansbury; Shaul Barth; Gabi Tarcic; Eric B. Kmiec (Elsevier, 2020)
CRISPR and associated Cas nucleases are genetic engineering tools revolutionizing innovative approaches to cancer and inherited diseases. CRISPR-directed gene editing relies heavily on proper DNA sequence alignment between the guide RNA (gRNA)/CRISPR complex and its genomic target. Accurate hybridization of complementary DNA initiates gene editing in human cells, but inherent gRNA sequence variation that could influence the gene editing reaction has been clearly established among diverse genetic populations. As this technology advances toward clinical implementation, it will be essential to assess what degree of gRNA variation generates unwanted and erroneous CRISPR activity. With the use of a system in which a cell-free extract catalyzes nonhomologous end joining (NHEJ) and homology-directed repair (HDR), it is possible to observe a more representative population of all forms of gene editing outcomes. In this manuscript, we demonstrate CRISPR/Cas complexation at heterologous binding sites that facilitate precise and error-prone HDR. The tolerance of mispairing between the gRNA and target site of the DNA to enable HDR is surprisingly high and greatly influenced by polarity of the donor DNA strand in the reaction. These results suggest that some collateral genomic activity could occur at unintended sites in CRISPR-directed gene editing in human cells.